Первая находка неогеновой росомахи Plesiogulo crassa в Северном Причерноморье - Короткевич, Е.Л.; Семенов, Ю.А. (Вестник зоологии, 1975)
The fossil Plesiogulo crassa previously known only from the Asian Neogene is registered first in the composition of Late Miocene Hipparion fauna of the Northern Black Sea area. A description of the craniological material is given. It is pointed out that this species cannot be a direct ancestor of the modern genus Gulo because of different direc- tion of its chewing apparatus specialization. On the basis of the Plesiogulo findings in the territory of the USSR some remarks. are made concerning the genus composition and its phylogeny.